The application of Maqasid al-Shari'ah in medicine: an overview - Hashi, Abdurezak Abdulahi (IIUM Journal Publication Unit, 2019)
Maasid al-shari’ah or the objectives of the Islamic law and medicine share inherent intersections, and sometimes work as integral subjects, the ultimate aim of which is “harm reduction” and “promotion of wellbeing” in life. The maqasid al-shari’ah does this by providing values and principles of good conducts, while medicine achieves this aim through practical and hands on healthcare services. The paper uses analytical method and presents a concise overview of the Islamic medical ethics, with the focus on the applications of maqasid al-shari’ah in medical services. Besides the literature review, the paper highlights the basic contents and fields of both medicine and objectives of the Islamic law. The paper then identifies and analyses eleven areas of medical practices in which the values of maqasid al-shari’ah can be applied. Conclusions drawn from these analyses are illustrated at the end of the paper.